2016
DOI: 10.18632/oncotarget.8430
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor beta increases migration of human bladder cancer cells

Abstract: Bladder cancer is observed worldwide having been associated with a host of environmental and lifestyle risk factors. Recent investigations on anti-inflammatory glucocorticoid signaling point to a pathway that may impact bladder cancer. Here we show an inverse effect on the glucocorticoid receptor (GR) isoform signaling that may lead to bladder cancer. We found similar GRα expression levels in the transitional uroepithelial cancer cell lines T24 and UMUC-3. However, the T24 cells showed a significant (p < 0.05)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 55 publications
0
45
0
Order By: Relevance
“…GR␤, however, has a truncated helix 12 and is missing the ligand binding pocket known to bind to GCs (3). The known function of GR␤ is to act as a dominant-negative antagonist to GR␣ (3,5,(7)(8)(9). We have previously shown that GR␤ mRNA increased from fasting and refeeding in the livers of mice (8).…”
mentioning
confidence: 99%
“…GR␤, however, has a truncated helix 12 and is missing the ligand binding pocket known to bind to GCs (3). The known function of GR␤ is to act as a dominant-negative antagonist to GR␣ (3,5,(7)(8)(9). We have previously shown that GR␤ mRNA increased from fasting and refeeding in the livers of mice (8).…”
mentioning
confidence: 99%
“…GRβ lacks the ligand-binding domain for glucocorticoids (Hinds et al, 2010) and has been indicated to inhibit GRa (Leung et al, 1997;Hinds et al, 2010;Kubin et al, 2016). GRβ has been demonstrated to be involved in the migration of bladder cancer and brain cancer (Mcbeth et al, 2016;Ying et al, 2013), and some other studies have also reported that GRβ levels are elevated in inflammatory diseases and cancers, leading to increased progression (Zhu et al, 2007;Marino et al, 2016;Psarra et al, 2005). Hence, we hypothesise that the poor prognosis of patients with the rs12682421 A allele may be associated with a higher GRβ expression.…”
Section: Discussionmentioning
confidence: 87%
“…27,28 Furthermore, this isoform was found to participate in the molecular pathways of glioma formation as well as in the migration of bladder cancer cells. [29][30][31] In addition to in vitro and animal experiments, studies in humans have shown that hGRβ expression levels are associated with glucocorticoid resistance in severa l inflammatory diseases (ulcerative colitis, rheumatoid arthritis, systemic lupus erythematosus, asthma), hematologic malignancies (acute lymphoblastic leukemia, chronic lymphocytic leukemia) as well as in many mood disorders (major depression, schizophrenia). 18,32 In contradistinction to hGRβ, the hGRα isoform is ubiquitously expressed in every tissue except the SCN Figure 1.…”
Section: Glucocorticoid Receptor: From the Nr3c1 Gene To Protein Isofmentioning
confidence: 99%